Pengaruh Inokulasi Cacing Tanah (Pontoscolex corethrurus Fr Mull) Terhadap Sifat Fisika Kimia Tanah dan Pertumbuhan Tanaman Kacang Hijau (Vigna radiata L.Wilczek) Varietas Walet - Adianto Adianto; Diah Utami Safitri; Nuryati Yuli (Jurnal Matematika & Sains, 2004)
The effect of earthworm inoculation on soil physical and chemical properties and the growth of mung bean inexperimental pot had been studied. Earthworms were inoculated at four different densities i.e. 0 (Co), 4 (C4), 8 (C8)and 12 (C12)individuals in pots containing clay : humus : sand (5 :3 : 2) dry weight and kept for 120 days. Cowdung were applied ad libitum. The control (without earthworms inoculation) consisted of two groups ; with andwithout dung ( Co- and Co+). The results of this experiment indicated that the rate of microorganism respirationwas highest in C12 treatment and significantly different (p < 0,05) from Co- and Co+. Cellulose decompositionlevel was also highest in C12 treatment compared to Co-. Soil physical analysis indicated that total porosityincreased significantly in C8 and C12 treatment compared to Co- and Co+ . Water permeability increasedsignificantly in C4 treatment compared to Co-. Soild chemical analysis indicated that soil pH increased due toearthworm inoculation. Organic Carbon decrease in accordance with the increasing number of earthworm, thehighest decreaseng in C12 treatment and the lowest in Co-. The N,P,K,Ca and Mg level increased in all treatmentscompared to Co-.. The plant height increased significantly in C8 and C12 treatment compared to Co- and Co+.Furthermore plant biomass increased significantly in treatment C12 compared to Co- and Co+. It can beconcluded that inoculation with earthworms could change the soil physical and chemical properties and improvedconditions for the growth of mung bean.